A systematic assessment of mycobacterial F1‐ATPase subunit ε's role in latent ATPase hydrolysis. (4th July 2020) - Wong, Chui‐Fann; Lau, Aik‐Meng; Harikishore, Amaravadhi; Saw, Wuan‐Geok; Shin, Joon; Ragunathan, Priya; Bhushan, Shashi; Ngan, So‐Fong Cam; Sze, Siu Kwan; Bates, Roderick W.; Dick, Thomas; Grüber, Gerhard
Abstract : In contrast to most bacteria, the mycobacterial F1 FO ‐ATP synthase (α3 :β3 :γ:δ:ε: a : b : b' : c9 ) does not perform ATP hydrolysis‐driven proton translocation. Although subunits α, γ and ε of the catalytic F1 ‐ATPase component α3 :β3 :γ:ε have all been implicated in the suppression of the enzyme's ATPase activity, the mechanism remains poorly defined. Here, we brought the central stalk subunit ε into focus by generating the recombinant Mycobacterium smegmatis F1 ‐ATPase ( Ms F1 ‐ATPase), whose 3D low‐resolution structure is presented, and its ε‐free form Ms F1 αβγ, which showed an eightfold ATP hydrolysis increase and provided a defined system to systematically study the segments of mycobacterial ε's suppression of ATPase activity. Deletion of four amino acids at ε's N terminus, mutant Ms F1 αβγεΔ2‐5, revealed similar ATP hydrolysis as Ms F1 αβγ. Together with biochemical and NMR solution studies of a single, double, triple and quadruple N‐terminal ε‐mutants, the importance of the first N‐terminal residues of mycobacterial ε in structure stability and latency is described. Engineering ε's C‐terminal mutant Ms F1 αβγεΔ121 and Ms F1 αβγεΔ103‐121 with deletion of the C‐terminal residue D121 and the two C‐terminal ɑ‐helices, respectively, revealed the requirement of the very C terminus for communication with the catalytic α3 β3 ‐headpiece and its function in ATP hydrolysis inhibition. Finally, we applied the tools developed during the study for an in silico screen to identify a novel subunit ε‐targeting F‐ATP synthase inhibitor. Abstract : In contrast to most bacteria, the mycobacterial F1 FO ‐ATP synthase (α3 :β3 :γ:δ:ε: a : b : b' : c9 ) does not perform ATP hydrolysis‐driven proton translocation. Here, genetic, biochemical and NMR solution studies demonstrate the importance of mycobacterial ε in structure stability and ATP hydrolysis suppression. Finally, we applied the tools developed during the study for an in silico screen to identify a novel subunit ε‐targeting F‐ATP synthase inhibitor.